Rapid identification of gutter oil by detecting the capsaicin using surface enhanced Raman spectroscopy. (18th December 2017) - Tian, Kangzhen; Wang, Wen; Yao, Yue; Nie, Xinming; Lu, Aixia; Wu, Ying; Han, Caiqin
Abstract: Accurate determination of the gutter oil represents a major food safety challenge. Here, we propose to use the surface enhanced Raman spectroscopy (SERS) with silver nanorod array substrates to detect the capsaicin, a marker of the gutter oil that is difficult to remove. The capsaicin has several characteristic SERS peaks at Δv = 807 cm −1, Δv = 1, 264 cm −1, and so forth, which correspond to the C39 ‐C37 ‐C43 stretching vibrational mode at the alkyl chain, the ring stretching vibrational mode, and so forth, confirmed by our density functional theory calculation. This SERS‐based method enabled the rapid and highly sensitive detection of the gutter oil with minimum pretreatment. The concentration dependent SERS investigation shows that the SERS intensity of these characteristic peaks has a linear relationship with the capsaicin concentration when 1 mg/L < C < 60 mg/L. By combining a liquid phase extraction method and the SERS detection strategy, the capsaicin concentration as low as 30 mg/L can be detected from inoculated corn oil samples. Abstract : A sensitive surface‐enhanced Raman spectroscopy (SERS) method with silver nanorod array substrates was explored for quantification of capsaicin in gutter oil. This SERS‐based method enabled the rapid and highly sensitive detection of the gutter oil with minimum pretreatment. By combining a liquid phase extraction method and the SERS detection strategy, capsaicin concentration as low as 30 mg/L can be detected from inoculated corn oil samples.